2022
DOI: 10.1186/s12884-022-05062-7
|View full text |Cite
|
Sign up to set email alerts
|

Teenage first-time mothers’ perceptions about their health care needs in the immediate and early postpartum period in Uganda

Abstract: Background Teenagers have higher risks for complications during the intrapartum and postpartum periods. Although facility-based postpartum care focusses on preventing complications in mothers and babies, it is not understood what teenage-mothers’ perceptions are about their health care needs in the early postpartum period. Methods An exploratory descriptive qualitative study was conducted in four health facilities in Uganda. In-depth interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Furthermore, a systematic review on guideline use in low income countries found that knowledge and dissemination of the guidelines did not translate into their use during management of patients [ 39 41 ]. Other Ugandan studies have noted that, patients are not monitored, examined or health educated as stipulated when guidelines are inconsistently implemented [ 42 , 43 ]. The main reasons for the failure to adhere to recommended guidelines are related to incomplete training coverage; inadequacies in setting up local standards, champions and leadership.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a systematic review on guideline use in low income countries found that knowledge and dissemination of the guidelines did not translate into their use during management of patients [ 39 41 ]. Other Ugandan studies have noted that, patients are not monitored, examined or health educated as stipulated when guidelines are inconsistently implemented [ 42 , 43 ]. The main reasons for the failure to adhere to recommended guidelines are related to incomplete training coverage; inadequacies in setting up local standards, champions and leadership.…”
Section: Discussionmentioning
confidence: 99%